The Relationship Between Chinese English Major Students' Learning Anxiety and Enjoyment in an English Language Classroom: A Positive Psychology Perspective - Fang, Fan; Tang, Xiaofei (Frontiers in Psychology, 2021)
Many studies have explored learner psychology in relation to second language acquisition (SLA) in order to understand the effectiveness and difficulties of language learning. In the last two decades, emotional factors in students’ language learning have garnered much attention in the field of SLA. However, more recently, studies have begun to focus on enjoyment and its relationship with anxiety. By collecting data at a provincial key university in southeast China, the study discussed in this paper investigated English major university students’ emotions related to learning English. By collecting questionnaire responses from 140 English major undergraduates and conducting interviews with six students, the findings revealed that the participants’ levels of foreign language enjoyment (FLE) were significantly higher than their levels of foreign language classroom anxiety (FLCA) and that they experienced FLE more frequently than FLCA. It was also found that the participants’ FLE was more related to their teachers and peers and their FLCA was more related to their emotions, such as fear of a negative evaluation and speaking without sufficient preparation. In addition, this study also provides a few pedagogical implications for improving foreign language learning outcomes and teaching efficiency in English teaching and learning.